ASEAN’s climate change mitigation and adaptation measures: abandoning stagnant policy responses - Putra, Bama Andika (Frontiers in Climate, 2024)
Southeast Asia is one of the most at-risk regions when it comes to the impacts of climate change. Densely populated cities and the increasing dependency of the Southeast Asian population on coastal areas make the risk of sea-level rise more prominent for the region. The Association of Southeast Asian Nations (ASEAN) has not been able to match this growing threat with the lack of ideal collective action in terms of mitigating and adapting to climate change. The reliance on the ASEAN State of Climate Change Report and vast ASEAN sectoral bodies have shown stagnant progress. This policy brief recommends (1) imposing adaptation and mitigation measures for ASEAN member states to adopt and (2) elevation of the “climate change’ discourse within ASEAN’s bodies into the category of “existential threat” to abandon ASEAN’s current risk-based perception vis-à-vis climate change. The actionable recommendation for ASEAN would be dependent upon whether the proposed mechanism ensures an alignment with the ASEAN Way (non-interference and consensus in decision-making).